MANAJEMEN KURIKULUM TAHFIDZ AL-QUR’AN DI SMP TMI ROUDLOTUL QUR’AN METRO DAN SMP IT BAITUNNUR PUNGGUR DALAM PENCAPAIAN TARGET HAFALAN AL-QUR’AN - Naila Rahmah Salsabila; Agus Pahrudin; Amirudin Amirudin (STKIP Pesisir Selatan, 2026)
This study aims to analyze the management of the Qur’an memorization (tahfidz) curriculum in achieving students’ memorization targets at SMP TMI Roudlotul Qur’an Metro and SMP IT Baitunnur Punggur. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The results indicate that the tahfidz curriculum management in both schools has been implemented through systematic planning, implementation, and evaluation with different approaches. The boarding school system is more effective in achieving memorization targets due to intensive learning, a supportive environment, and continuous supervision. Meanwhile, the non-boarding system remains effective through curriculum integration strategies and efficient time management. Supporting factors include the learning environment, teachers’ roles, and parental involvement, while obstacles include limited time and differences in students’ abilities.